(3GdbHV Ydi GdeJge eGgjJg (B- (3GMcGeg (B- (3GKGQg (B: s (3OQGSI ebGQfI (B/ s - (3eMehO YHOGdMSjH GMeO WdHg GdYQjfis; (3MSfjf YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3GdGUd ai GdbHV Gfg dG jLhR GdG ai GdLQGFe GdJi jLhR ajgG MHS GdeJge GMJjGWjG (B: (3GdG Gf GdeTQY GdeUQi GLGR dbGVi GdJMbjb Gf jUOQ GeQG HGdbHV Ydi GdeJge h GMVGQg (B: (3hdh cGfJ GdhGbYI eeG dG jLhR ajgG MHS GdeJge GMJjGWjG (B: (3GPG de jMVQ GdeJge HYO Jcdjag HGdMVhQ Ohf YPQ ebHhd (B: (3Gh GPG Nja gQH GdeJge (B: (3Gh GPG de jcf ddeJge eMd GbGeI eYQha (B: (3Gh GPG cGfJ GdLQjeI ai MGdI JdHSs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B401-429s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdbHV Ydi GdeJges; (3GdeTQY GdeUQis; (3MGdI GdJdHSs; (3PGJjI GdbHVs; (3GdGSJjbGas; (3HWdGf GdbHVs; (3GdGLQGA GdHGWds; (3GdhSGFd GdYdejI aj JaJjT GdeJges; (3GdJdHSs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs